1996
DOI: 10.3354/meps131017
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting spatial variability in seine net catches of fish in the surf zone of False Bay, South Africa

Abstract: Ichthyofaunal assemblages at 11 surf zone localities along the perimeter of False Bay South Afnca were sampled by seine netting at monthly intervals between July 1991 and J u n e 1993 Sampllng localit~es were selected to encompass as wide a range of physical vanables as possible incorporatlng sheltered, exposed, sandy and mixed-shore habitats, thus providing a colnprehensive assessment of the factors lnfluenclng surf zone fish assemblages Data collected at each site were averaged over the 2 yr p e i~o d in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
2
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 46 publications
(74 reference statements)
2
55
2
6
Order By: Relevance
“…Isto pode ser decorrente de variações no período de atividade das espécies, uma vez que as coletas foram realizadas apenas no período diurno. A sucessão dos dias e noites produz uma oscilação da maioria dos fatores ambientais de interesse ecológico (Margalef 1986), que influenciam a abundância relativa de certas espécies, alterando a composição e a riqueza nas assembléias de peixes (Clark et al 1996). A importância das áreas rasas costeiras no ciclo de vida dos peixes foi demonstrada por Lenanton (1982) que ressaltou a importância de tais áreas para peixes jovens em praias costeiras da Austrália.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Isto pode ser decorrente de variações no período de atividade das espécies, uma vez que as coletas foram realizadas apenas no período diurno. A sucessão dos dias e noites produz uma oscilação da maioria dos fatores ambientais de interesse ecológico (Margalef 1986), que influenciam a abundância relativa de certas espécies, alterando a composição e a riqueza nas assembléias de peixes (Clark et al 1996). A importância das áreas rasas costeiras no ciclo de vida dos peixes foi demonstrada por Lenanton (1982) que ressaltou a importância de tais áreas para peixes jovens em praias costeiras da Austrália.…”
Section: Discussionunclassified
“…A ação das ondas, considerada como sinônimo de exposição, é um dos fatores primários mais importantes no controle das características físico-químicas na zona de arrebentação (McLachlan 1980). Essa variável ambiental tem uma importante contribuição na composição e estrutura da comunidade íctica (McLachlan et al 1984, Dexter 1990, Clark et al 1996, Clark 1997, devido ao estresse físico local decorrente do quebrar das ondas, afetando a modificação da estrutura do sedimento e/ou as fontes de alimentos (Bennett 1989).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…As an important beach modeler (Hoefel, 1998) and transporter of organic matter and nutrients between continent and sea (Yañez-Aranciabia, 1978), the surf-zones support a widely fauna, mainly zooplankton and fishes (Maes et al, 1998). In fact, it has been observed that environmental complexity in terms of wave exposure and microhabitats formation, like seagrass and reefs, are related to composition and dynamics of surf-zone fish assemblages (Clark et al, 1996;Clark, 1997). Surf-zone ichthyofauna are both seasonal and diel dynamic (Modde and Ross, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the incident light exerts influence on the abundance of many species, changing in the composition and richness of fish assemblages (Clark et al, 1996). These changes in fish community may be associated with the use of the sandy beach at different times of the day.…”
Section: Introductionmentioning
confidence: 99%